The Impact of Span Width and Outrigger Shape on Fishing Boats at Palabuhanratu Fishing Port, Indonesia - Malik, Fikri Rizky; Novita, Yopi; Iskandar, Budhi Hascaryo; Puspito, Gondo; Sukoraharjo, Sri Suryo (Institut Teknologi Sepuluh Nopember, 2024)
Outrigger boats are prevalent in Indonesian waters. In Indonesia, the majority of Outrigger boats have a gross tonnage of less than 7 GT, resulting in their classification as